The response of salivary proinflammatory biomarkers to tooth extraction in individuals with type II diabetes mellitus - Yousuf Ibrahim Al Shehhi; Noha M. Elemam; Mohammed Amjed Alsaegh (BMC Oral Health, 2024)
Abstract Purpose This study investigated the levels of salivary proinflammatory cytokines in the saliva of patients living with type II diabetes mellitus (DM) compared to those in healthy individuals three times: before tooth extraction and at 2 hours and 2 days after tooth extraction. Methods The study included 27 participants. Among them, 20 (n = 20; 74%) had type II DM, and seven (n = 7; 26%) were healthy control subjects. Saliva samples were collected at three time intervals: before tooth extraction and 2 hours and 2 days after tooth extraction. The salivary biomarkers were investigated using a Luminex multiplex assay. These salivary biomarkers included tumor necrosis factor-alpha (TNF-α), interleukin 6 (IL-6), interleukin 1-beta (IL-1β), and interferon-gamma (IFN-γ). Results At baseline, patients with type II DM had significantly lower levels of IL-1β (P = 0.016). Moreover, 2 hours after extraction, patients with type II DM had significantly lower levels of IL-1β and TNF-α than did healthy control subjects (P = 0.046 and P = 0.020, respectively). In addition, 2 days after tooth extraction, the DM group had significantly greater IL-6 levels (P = 0.010) than the control group. Conclusions In patients with type II DM, salivary proinflammatory biomarker levels are generally comparable or lower than those in healthy control subjects. Proinflammatory cytokines manifest differently in patients with type II DM after tooth extraction than in normal healthy individuals. There is generally a delayed early response of salivary proinflammatory markers in patients living with type II DM who undergo tooth extraction.